Pembelajaran Problem Solving Model Abell Dan Pizzini Pada Siswa SMK Dalam Konteks Pengaktifan Kerja Sabun Pembersih Badan - Khairat, Nasibatun Umul (2014)
This research study titled problem solving Abell and Pizzini models in the context of activation soap body work on vocational students. This study aimed to obtain information on the feasibility study the Abell and Pizzin -type problem solving in the context of activation soap work and problem solving skills of students in solving real-life problems by applying the concepts at work activation soap. The subjects of the study consisted of 31 students of class XII at SMKN 1 in Baleendah. This study used a descriptive method. The instruments used research are Instrument Teacher Performance (ITP) I and II, worksheets of assessment instruments, test items, affective assessment and performance assessment sheets. The results obtained in this study indicate that the learning problem solving type Abell and Pizzini seen from the competence of teacher in planning and implementing learning is very well belong to the category. Viewed from the side of the students during the learning aspect which is reviewed through the problem solving ability, problem solving ability of students to identify the problem phase, design investigation phase, analyzing data phase, raise findings phase, presenting the findings phase, and evaluating phase are intermediate belong to the category. The attitude of the students during the learning, and the student's performance during the experiment are in excellent condition. Smoothing problems phase classified in low category. Stage collect data relatively high category, as a whole that the problem solving ability of students classified categories are (n-gain = 0.4). Thus the process of Abell and Pizzini problem solving type in the context of work soap body cleanser activation can be applied as learning in school to apply the material that being taught.